(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
Fibrils represent the first level of collagen structure visible from using scanning electron microscopy. Collagen fibril is stabilized by the formation of two types of chemical bonds: salt connections and covalent intermolecular connections. Salt connections are electrostatic bonds formed between acidic and basic functional groups on the side chains amino acids whose strength is maximized by alignment polar regions of fibrils.